The life of Hinduism - Hawley, John Stratton; Narayanan, Vasudha (The life of religion, 2006)
'The Life of Hinduism' collects a series of essays that present Hinduism as a vibrant, truly 'lived' religion. The text offers a glimpse into the multifaceted world of Hindu worship, life-cycle rites, festivals, performances, gurus, and castes